Ultra-high frequency, high Q/volume micromechanical resonators in a planar AlN phononic crystal - Baboly, M. Ghasemi; Alaie, S.; Reinke, C. M.; El-Kady, I.; Leseman, Zayd Chad (My University, 2016)
This paper presents the first design and experimental demonstration of an ultrahigh frequency complete phononic crystal (PnC) bandgap aluminum nitride (AlN)/air structure operating in the GHz range. A complete phononic bandgap of this design is used to efficiently and simultaneously confine elastic vibrations in a resonator. The PnC structure is fabricated by etching a square array of air holes in an AlN slab. The fabricated PnC resonator resonates at 1.117 GHz, which corresponds to an out-of-plane mode. The measured bandgap and resonance frequencies are in very good agreement with the eigen-frequency and frequency-domain finite element analyses. As a result, a quality factor/volume of 7.6 x 10(17)/m(3) for the confined resonance mode was obtained that is the largest value reported for this type of PnC resonator to date. These results are an important step forward in achieving possible applications of PnCs for RF communication and signal processing with smaller dimensions. Published by AIP Publishing.
Citation: Baboly, M. G., Alaie, S., Reinke, C. M., El-Kady, I., & Leseman, Z. C. (2016). Ultra-high frequency, high Q/volume micromechanical resonators in a planar AlN phononic crystal. Journal of Applied Physics, 120(3), 5. doi:10.1063/1.4958671
Keywords: Wave-Guides; Optomechanical Cavity; Acoustic-Waves; Band-Gaps; Design; Physics